2017
DOI: 10.2146/ajhp160737
|View full text |Cite
|
Sign up to set email alerts
|

Management of amiodarone extravasation with intradermal hyaluronidase

Abstract: Administration of intradermal hyaluronidase after amiodarone extravasation was associated with decreased expansion of erythema and warmth as well as an improvement in patient-reported pain scores without any noted adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Rowllet et al reported human hyaluronidase injection for extravasation of contrast media in a circle around the wound, which led to improvements during 4 h [ 22 ]. Fox et al illustrated wound enhancement after injection of hyaluronidase following amiodarone extravasation without any complications [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rowllet et al reported human hyaluronidase injection for extravasation of contrast media in a circle around the wound, which led to improvements during 4 h [ 22 ]. Fox et al illustrated wound enhancement after injection of hyaluronidase following amiodarone extravasation without any complications [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hyaluronidase has been used for the treatment of hyperosmolar and pH‐related mechanisms of injury with success previously reported in managing TPN, calcium, radiographic contrast media, dextrose, potassium, mannitol, aminophylline, nafcillin, and phenytoin extravasations 4 . Amiodarone is the newest agent with reported success for the treatment of extravasation‐related pain with hyaluronidase 53 . Hyaluronidase can be administered at 15 units/mL (up to 150 units) in five divided doses (0.2 mL) injected subcutaneously around the site of extravasation or intravenously through the infiltrated catheter (Table 3).…”
Section: Pharmacological Treatment and Supportive Carementioning
confidence: 99%
“…He received intradermal hyaluronidase administration within 24 hours of developing severe pain from extravasation induced by amiodarone with no adverse outcomes and full recovery. 7 There are numerous properties of amiodarone that may have resulted in the skin necrosis seen in these cases. The acidic pH (3.5-4.5) of amiodarone can contribute to coagulative necrosis, cellular desiccation, eschar formation, and edema.…”
Section: Hyaluronidase For Skin Necrosis Induced By Amiodaronementioning
confidence: 99%
“…10 Extravasation of amiodarone can be treated nonpharmacologically with limb elevation and warm compresses, as these methods may promote vasodilation and enhance drug removal. [5][6][7] However, when extravasation leads to progressive erythema and skin necrosis or is refractory to these therapies, intradermal injection of hyaluronidase should be considered. Hyaluronidase mediates the degradation of hyaluronic acid in the extracellular matrix, allowing for increased permeability of injected fluids into tissues and diluting the concentration of toxins at the site of exposure.…”
Section: Hyaluronidase For Skin Necrosis Induced By Amiodaronementioning
confidence: 99%
See 1 more Smart Citation